Data Visualisation as a Tool for Informed Structural Design. (October 2019) - Loos, Lennert; Verbeeck, Kenny; De Laet, Lars
Abstract: The architectural design process is characterised by continuously comparing different design alternatives throughout the whole design process. Collaborators from different fields of expertise need to work closely together and they are expected to give quick but sufficient feedback on the available design alternatives in order to proceed in the collaborative process. However, for structural engineers making these comparisons on the structural behaviour and efficiency is hard to do. The lack of appropriate tools disables the structural engineer to gain quickly and qualitatively insight into a set of design alternatives. This paper discusses a novel mind-set for structural designers, that fills this gap by informed decision-making based on data visualisation. This kind of data exploration is only rarely used in the structural design field. Since visual displays of data allow for better decision-making, this opportunity should be leveraged by structural designers. Five different bow-string bridge geometries are compared as a case study with the help of data visualisation. As a consequence, this paper focuses on the comparing practice of structural parametric models of the same structural typology. This research illustrates that the use of data visualisations can help designers to quickly understand the structural behaviour and performance of different design alternatives. This way, informed decision-making through comparing is facilitated. Graphical abstract: Highlights: A new approach for informed structural design by means of data visualisations is proposed. New graphs for comparing structural behaviour and performance are discussed. By a case study on bow-string bridges, the method is illustrated with various graphs. This new approach allows a real-time designer feedback for exploring the design space.